Electric‐Field Assisted In Situ Hydrolysis of Bulk Metal–Organic Frameworks (MOFs) into Ultrathin Metal Oxyhydroxide Nanosheets for Efficient Oxygen Evolution. (26th May 2020) - Tian, Jiayue; Jiang, Feilong; Yuan, Daqiang; Zhang, Linjie; Chen, Qihui; Hong, Maochun
Abstract: Facile preparation of low‐cost electrocatalysts for efficient oxygen evolution reaction (OER) remains a big challenge. Herein, a novel strategy for ultrafast (20 s) transformation of bulk metal–organic frameworks (MOFs) into ultrathin metal oxyhydroxide nanosheets for efficient OER has been developed. For two isomeric MOFs (FJI‐H25Fe and FJI‐H25FeCo ), only the metastable FJI‐H25FeCo bulk can immediately transform into FeCo‐oxyhydroxides nanosheets through electric‐field assisted hydrolysis. The potential evolution process from MOF bulk to FeCo‐oxyhydroxides nanosheets has been investigated in detail. The as‐made nanosheets exhibit excellent OER performances, showing an extremely low overpotential of 231 mV at the current density of 10 mA cm −2, a relatively small Tafel slope of 42 mV dec −1, and long‐term durability of at least 30 h. This work not only provides a novel strategy for facile preparation of low‐cost and efficient OER electrocatalysts, but also represents a new way for preparation of metal oxyhydroxides nanosheets with good crystallinity and morphology, and a fresh method for mild synthesis of nanosized derivatives from MOF materials. Abstract : Think thin : Ultrafast transformation of bulk metal–organic framework (MOF) into ultrathin metal oxyhydroxide nanosheets through electric‐field hydrolysis is possible. The nanosheets exhibit excellent oxygen evolution reaction (OER) performances. The potential evolution process from bulk MOF to FeCo‐oxyhydroxides nanosheets has been investigated in detail.